Association of Serum Vitamin D Levels on Response Therapy in Patient Lung Adenocarcinoma Advanced with Targeted Therapy (Medico Legal Update, 2021)
Objective: This study aimed to analysis the associated of serum vitamin D levels and response therapyin advanced lung adenocarcinoma patient after used TKIs. Methods: This study was an observationalanalytic study. The subjects where patient with advanced lung adenocarcinoma who received tyrosine kinaseinhibitors (TKIs) for 3 months at Dr. Soetomo general hospital Surabaya from July to March 2021 who metthe inclusion and exclusion criterias. The independent variable in this study are the serum levels of vitaminD and response therapy objective (RECIST criteria) as the dependent variable. Results: The results ofstastitical analysis showed that there was no significant associated of serum vitamin D levels and responsetherapy (p>0.05). Patient insufficiency with partial response had a greater number than patient sufficiencywith partial response. The mean of vitamin D levels in patient with progressive disease was the highest.Conclusion: Although the serum levels of vitamin D in lung cancer was lower but in this study showed thatthere was no significant associated of serum vitamin D levels and response therapy in patient advanced lungadenocarcinoma with tyrosine kinase inhibitors.